The legend of Luke - Jacques, Brian; Fangorn (New York : Philomel Books, 2000)
When Martin the Warrior leaves Redwall Abbey and embarks upon a journey to the place of his birth, he learns about the brave and noble deeds of his father Luke, a real Warrior Chieftain.
A tale of Redwall.
Keywords: Mice -- Fiction; Animals -- Fiction; Fantasy